2020
DOI: 10.21608/ijma.2020.33846.1140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Manifestation of ototoxic medications among the adult attendees of the Audio-vestibular unit at Al-Zahraa University hospital, Cairo, Egypt

Abstract: Background: Hearing loss is considered to be one of the most common factors of moderate to severe disability specially in the developing countries. Ototoxicity is inner ear damage due to usage of chemical substances, which can lead to either reversable or permanent hearing loss and/or vestibular loss. Ototoxic hearing impairment can impact the quality of life by many ways; therefore, we should be very careful when it comes to choose drug therapy to minimize the risk. Aim of the work:To identify the commonly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results showed a prevalence of 10-15% among adults. Similarly, results from studies in Egypt [182,183], Japan [184][185][186], and Nigeria [187,188], also indicated that the rate of prevalence of tinnitus in these countries is analogous to the results from the Europe [189] and the USA [190][191][192].…”
Section: Tinnitusmentioning
confidence: 63%
“…The results showed a prevalence of 10-15% among adults. Similarly, results from studies in Egypt [182,183], Japan [184][185][186], and Nigeria [187,188], also indicated that the rate of prevalence of tinnitus in these countries is analogous to the results from the Europe [189] and the USA [190][191][192].…”
Section: Tinnitusmentioning
confidence: 63%